Psychoanalytic theory for social work practice : thinking under fire - Bower, Marion (Routledge, 2005)
It gives me great pleasure to write a preface for this book, which I hope will make asignificant contribution to the further development of social work in Britain and othercountries. The book is published at an important moment in the history of the social workprofession in Britain. For the first time social care workers are now part of a registeredprofession. In past decades the question of professional registration was often a subject ofheated debate between those who were convinced of its need if social work was toestablish itself within the multidisciplinary professional field, and those w
Keywords: Social service; Psychoanalysis